Sustainable Energy Mix in Fragile Environments Frameworks and Perspectives (Social and Ecological Interactions in the Galapagos Islands,, 2018)
The purpose of this book is to present a range of cases and comparison of the issues, insights and cases emerging from the Sustainable Energy Mix Summit in the Galapagos that offer a better understanding of energy mix in fragile environments from a variety of International locations and contexts including the Galapagos. .